Ekokritika i Zarobljenik šumske kuće Anđelke Martić u izdanju Eko Vjeverice ( Ecocriticism and Anđelka Martić’s Prisoner of the Forest House in Eco Squirrel Book Series ) - Batinić, Ana (Poznańskie Studia Slawistyczne, 2022)
The introductory part of the article aims to briefly present the main ideas of ecocriticism, a relatively new theoretical approach to the study of literary texts, and also provide basic information about a special publishing project launched at the beginning of the 1990s byMladost publishing house—Eko Vjeverica ( Eco Squirrel ), a book series intended for children. After that, the focus of the analysis is shifted to one of the titles from the series, Zarobljenik šumske kuće ( Prisoner of the Forest House ), a collection of stories written by a Croatian author Anđelka Martić. The main research issues in this article, which are at the same time the basic guidelines of ecocritical approach in the analysis of literary works, relate to the study of fundamental ecological values implied by the word “nature”—what nature is in a given context, in which way nature is experienced and perceived by human characters and how that perception has changed over the years, and also how the world around us acquires meaning through textual representations of nature.